The Effect of Entrepreneurial Skills and Self-Efficacy on Entrepreneurial Interest among Children - Suyadi, Suyadi; Septiarti, Serafin Wisni (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2025)
This study aims to determine the influence of entrepreneurial skills and self-efficacy on entrepreneurial interest in children. This research utilizes a quantitative approach with a meta-analysis. The inclusion criteria for this study include research published in national and international journals indexed by Sinta or Scopus; studies must be relevant, employ experimental or quasi-experimental methods, be published between 2020 and 2025, and provide complete data to calculate the effect size. Data collection is conducted through databases such as Google Scholar, Mendeley, Scopus, ERIC, and Wiley. Keywords: entrepreneurship skill; self-efficacy; the influence of entrepreneurial skills on entrepreneurial interest in children; the effect of self-efficacy on entrepreneurial interest in children. Data analysis is performed using the JASP application. The study concludes that there is a positive influence of entrepreneurial skills and self-efficacy on entrepreneurial interest in children, with a high value (r = 0.927; t = 8.718; p < 0.001) in the large effect size category. These findings provide important information for teachers to enhance children's entrepreneurial skills in schools.